THE ALTERATION OF BALANCE ON AGRICULTURE SECTOR IN CENTRAL JAVA PROVINCE AMIDST COVID-19 PANDEMIC - Sitti Retno Faridatussalam; Amalina Lutfi Razan; Riana Rika Rohmatin (Riset Ekonomi Pembangunan, 2021)
The infection of the Coronavirus (COVID-19) is tremendously massive, which has never been happened previously in the modern era. In the condition of uncertainty due to COVID-19, the agriculture sector becomes the guarantee to the fulfillment of food for 267 million Indonesian people. Even though the disruption towards food production and agriculture hasn’t been seen visibly in the field, the results of the analysis mentioned that the impact of COVID-19 infection will cause a limited food supply and an increase in price in the impacted area. For all this time, the agriculture sector is assumed as the only sector that could survive during the turmoil and crisis. In addition, agriculture is considered the strongest sector in maintaining the stability of Indonesian economics. This research aims to identify the performance of the agriculture sector in Central Java Province amidst the COVID-19 pandemic in the period of first to the third quarterly. The assessment applies the Input-Output analysis method. Secondary data are employed in this research. The study indicates that during the pandemic, the agriculture sector demonstrates the demand enhancement of final output, yet the household’s income and job opportunities are decreased, as recorded. It is due to this sector becoming a buffer by the existence of the COVID-19 pandemic since the agriculture sector can survive and becomes the focus of economics in Central Java.